KAJIAN FOCUS GROUP DISCUSSION (FGD) DALAM MITIGASI BENCANA TSUNAMI DI DESA PONCOSARI - Dwiatno, Achjat; Triadmadja, Radianta; Darmanto, Darmanto (Civil Engineering Forum Teknik Sipil, 2008)
Disaster mitigation require to be supported by information and data regarding the condition of local society characteristic and area. The available of correct information and data, expected can maximize usage of local resource, including labour, organization and material. One of the partisipative data collecting method able to be used to dig catastrophic society perception and understanding of tsunami is Focus Group Discussion ( FGD). Participant one of the important element in FGD, so that participant composition can influence attainment result of FGD. This research aim to know society characteristic and condition to formulate FGD participant criterion and composition in tsunami disaster mitigation. This Research type is descriptive research with approach qualitative, while primary data collecting use partisipative observation technique where researcher follow to involve and at the same time perceive FGD simulation execution. Discussant which uppermost enough is them owning catastrophic understanding and knowledge of tsunami nature, where this matter is influenced life experience or relate to its work responsibility. Several things which need to be paid attention in chosening and determining discussant: 1) education and age vary to start from student age until the old man with mean 35 year, 2) do not predominate by age, certain work or education, 3) if education of [him/ it] lower to be expected to have experience which enough or which is its old age, 4) entangling woman participant owning catastrophic understanding and knowledge of tsunami, 5) having work or got mixed up with interconnected activity or relate to natural disaster handling.